1997
DOI: 10.1177/152660289700400105
|View full text |Cite
|
Sign up to set email alerts
|

Changing Aneurysmal Morphology after Endovascular Grafting: Relation to Leakage or Persistent Perfusion

Abstract: Purpose: To relate changing abdominal aortic aneurysm (AAA) morphology after endovascular grafting to the presence of leakage, collateral perfusion, and other factors. Methods: Thirty-five patients who underwent successful AAA endovascular grafting were evaluated. Self-expanding Z-stents and Dacron grafts were applied in bifurcated and aortomonoiliac systems. Postoperative diameter changes were calculated from repeated spiral computed tomographic scans, angiograms, and ultrasonic phase-locked echo-tracking sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
94
4
3

Year Published

1999
1999
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(110 citation statements)
references
References 12 publications
9
94
4
3
Order By: Relevance
“…According to reports in the literature (3,10,11), leakages as a complication of endovascular aneurysms of the abdominal aorta occur in 2.4%-45.5% of cases. Leakages may originate at both the proximal and distal ends of the graft; these are so-called perigraft leaks according to the classification of White et al (10,11).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…According to reports in the literature (3,10,11), leakages as a complication of endovascular aneurysms of the abdominal aorta occur in 2.4%-45.5% of cases. Leakages may originate at both the proximal and distal ends of the graft; these are so-called perigraft leaks according to the classification of White et al (10,11).…”
Section: Discussionmentioning
confidence: 96%
“…The clinical importance of leakages remains unclear; however, some reports (2)(3)(4)(5) suggest that there is an increased risk of aneurysm rupture in association with them. Computed tomography (CT) is recognized as the most sensitive method of detecting leakages (6,7), but it often does not provide immediate evidence of their cause.…”
mentioning
confidence: 96%
“…The reported annual degree of neck enlargement is extremely variable: from <1 mm/year [10,14], to 1-2 mm/year [3,15,16] and over 2 mm/year [4,8,17]. There is an error of approximately 1-2 mm in the measurement procedure [3,7,18], and early neck dilatation is related to stent-graft oversizing [4,9].…”
Section: Discussionmentioning
confidence: 99%
“…While AAA sac maximal diameter shrinkage was initially received with enthusiasm, longer follow-up has demonstrated that this may be associated with later adverse effects upon the endograft including limb kinkage or occlusion, modular junctional separations, device migration, or related problems. [129][130][131] Such consequences of late morphologic changes to the AAA have been termed the "paradox of success." 117 Structural deterioration of endoluminal devices appears to increase with time and can also be a source of treatment failure.…”
Section: Endovascular Repairmentioning
confidence: 99%